The influence of corporate governance on intellectual capital efficiency: evidence from Islamic banks of OIC countries - Ejaz Aslam; Razali Haron (Asian Journal of Accounting Research, 2020)
The purpose of this study is to examine the impact of corporate governance (CG) on intellectual capital efficiency (ICE) in Islamic banks (IBs) of Organisation of Islamic Cooperation (OIC) countries.A sample of 129 IBs is drawn from the 29 OIC countries from 2008 to 2017. A two-step system of the generalised method of moments has been employed to account for the unobserved endogeneity and heteroscedasticity issue that arose due to time-variant and time-invariant variables.The results revealed that CG measures, namely board size, non-executive directors do explain the extent and quality of ICE in the expected direction. In contrast, CEO duality, Shariah board and audit committee are negatively associated with the ICE. Moreover, the authors observed that male CEO in IBs has negative, but foreign ownership has a positive association with ICE in determining the extent of ICE in IBs. This study contributes specifically to the stakeholder theory and the literature of ICE and CG.The findings of the study provide insight into how a larger board can overcome skill deficiency and how making more investment in ICE would help to enhance productivity. Hence, bank managers, regulators, policymakers and shareholders have strong interest in designing the appropriate CG structure to develop ICE in banks.This is one of the few studies which provide empirical evidence of CG mechanism to boost the ICE in the perspective of IBs of the OIC countries.